Evaluating Single Layer Graphene Micropatterns Induced by Ti:Sa Laser Irradiation. Issue 18 (25th June 2018) - Mortazavi, Somayeh; Mollabashi, Mahmoud; Barri, Rasoul; Nieto Pescador, Jesus; Gundlach, Lars; Smith, Joseph P.; Booksh, Karl S.; Shah, S. Ismat
Abstract : Due to the unique optical and electrical properties of graphene and its potential application in microelectronics and spintronics, precise micropatterning graphene on substrates has found significant attention for optimal performance of many these applications. This study investigates the process of patterning single layer graphene on a SiO2 /Si substrate using Ti:Sa laser irradiation. A variety of laser fluences are employed for the removal of graphene from the substrate surface as the film is scanned at different speeds and required laser fluences for the removal of graphene are determined at these speeds. This is performed because pulse overlapping is an effective parameter for successful removal of graphene from substrates, which results in different ablation thresholds for each laser scanning speed. Changes of produced channels widths are also investigated as a function of total laser fluences. Study of Raman spectra of patterned graphene film is performed by Raman microspectroscopy to evaluate the quality of laser produced micropatterns. It includes the investigations of intensity changes of defect D and D′ bands on graphene edge. Optical contrasts are also calculated for both graphene and graphene edge and the results are compared. Abstract : In this study, laser patterning of single layer graphene film is performed by Ti:sapphire laser irradiation. Micropatterns of different widths under various laser fluences and scanning speeds are produced. Intensities changes of defect D and D′ bands on graphene edge are investigated using Raman microspectroscopy. Moreover, optical contrast is calculated on patterns edge and compared with that of pristine graphene.